The effect of early exercise on intracranial pressure in neurocritical patients: a systematic review - Sayu Aryantari Putri Thanaya; Putu Eka Mardhika (Indoscholar, 2020)
Background: Neurocritical patients commonly present with increased intracranial pressure and are regularly treated with physiotherapy through exercise early after admission to the intensive care unit. However, the effect of exercise on intracranial pressure is minimally investigated, and there appears to be no systematic reviews or meta-analyses addressing this topic in the published literature. This study aimed to determine the effect of exercise on the intracranial pressure of neurocritical patients. Methods: Through a systematic review, literature searches on PubMed, PEDro, and CENTRAL were conducted in January 2020. The keywords used were: “physical therapy”, “physiotherapy”, “exercise”, “range of motion”, “intracranial pressure”, and “ICP”, combined using Boolean operators “OR” and “AND”. Only studies published in the English and Indonesian language were considered. Results: A total of five studies involving 193 patients (mean age 41-56 years old) were included in this review. Most included studies reported that intracranial pressure did not change significantly after passive range of motion exercise, and some studies found that intracranial pressure actually decreased significantly during and after passive range of motion and active exercise. An additional finding was that isometric exercise significantly increased mean intracranial pressure in patients with normal intracranial pressure. All studies reported that exercise could be used safely in patients. Conclusion: Exercise, in particular passive range of motion, does not increase the intracranial pressure of neurocritical patients and does not lead to any adverse effects, as long as isometric or Valsalva-like maneuvers are avoided.